Agricultural Credit Guarantee in Nigeria and the Uncertainties of the Macroeconomic Environment - Eyo, Emmanuel O.; Nwaogu, Merrian A.; Agenson, Michael E. (International Journal of Economics and Financial Issues, 2020)
Efforts to revitalize agricultural credit delivery became a reality in 1977 with the establishing of the Agricultural Credit Guarantee Scheme Fund. This study assesses the Agricultural Credit Guarantee Scheme (ACGS) under the Nigerian macroeconomic environment. It assesses the real value of loans guaranteed overtime; analyzes agricultural output in agriculture credit guarantee scheme, analyses the effect of changes in interest rate and other variables on the volume of loans guaranteed. Data obtained were analyzed using both descriptive and inferential statistics. This study suggests that the macroeconomic environment has not been friendly with ACGS operations. Credit guarantee contributes positively to increased agricultural output, but the number and value of loans guarantee as well as the performance of loans and agricultural sector output would be greatly enhance by policies that make interest rates, inflation, stock market capitalization, nominal exchange rates and other variables of the macroeconomic environment agricultural sector friendly and supportive. Keywords: Credit Guarantee, Agricultural Sector, Macroeconomic environment, Nigeria. JEL Classifications: H81 DOI: https://doi.org/10.32479/ijefi.9101